Arthritogenic potential of the 65 kDa stress protein--an experimental model. - Winrow, V R (1994)
OBJECTIVES--To assess the effect of an intra-articular presentation of stress (heat shock) proteins (hsp) on joint inflammation. METHODS--Wistar rats were sensitised with a suspension of heat killed Mycobacterium tuberculosis in oil in the scruff of the neck and challenged intra-articularly with stress protein or M tuberculosis preparations. Inflammation was assessed by joint swelling and, using immunohistology, cellular infiltration of the synovium and antibody induction by an enzyme-linked immunosorbent method. RESULTS--It was shown, for the first time, that the intra-articular administration of a recombinant myobacterial 65 kDa hsp can induce joint inflammation in M tuberculosis sensitised recipients; both powdered M tuberculosis and the purified protein derivative of tuberculin (PPD) produced a similar response, with T cell infiltration of the synovium and a time course typical of delayed type hypersensitivity. This response was specific to the 65 kDa protein as another immunodominant mycobacterial stress protein of 10 kDa was ineffective. Furthermore, intra-articular injection of the 65 kDa hsp induced an antibody response against both the 65 kDa and 10 kDa proteins and the antibody titres continued to rise when knee swelling had subsided. CONCLUSIONS--These results support the hypothesis that 60 kDa proteins are a relevant arthritogenic stimulus in an M tuberculosis background. Moreover, when antigen presentation occurs in the synovium of previously sensitised individuals, circulating antibodies are generated which persist and recognise cross-reactive epitopes on several stress proteins.